Pengaruh Nilai Wajar Aset Biologis terhadap Manajemen Laba - Vista Febryanti; Yosefa Sayekti; Aisa Tri Agustini (Universitas Jember, 2020)
The purpose of this study is to examine and analyze the effect of the biological asset’s fair value on the earning management in the agroindustry companies that listed at the Indonesia Stock Exchange (BEI). This research is a quantitative study using secondary data from annual and quarterly reports of agroindustry companies 2018. This study uses the dependent variable earning management which is measured by Stubben’s model, independent variable biological asset’s fair value which is measured by gains or losses from the implementation of fair value to biological assets, and control variables firm size (logarithm of total assets) and leverage (DER). The results of this study shows that the biological asset’s fair value which is implemented through the PSAK 69: Agriculture has the positive effect on the earning management, and control variables (firm size and leverage) have no effect on earning management. This results indicates that the implementation of biological asset’s fair value through PSAK 69 in agroindustry companies enhances earning management action taken by manager. Keywords: biological assets; earning management; fair value; PSAK 69.